2019
DOI: 10.11648/j.ajese.20190302.12
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Surface Water and Sediment of Silver River, Southern Ijaw, Bayelsa State, Niger Delta, Nigeria

Abstract: Water and sediment samples were collected from Silver River to determine the levels of various physicochemical parameters in both sediment and water from the river. This research was conducted with the aim of determining the extent of deterioration of the river as a result of artisanal refining of crude oil. The result obtained showed that the mean values of the different parameters examined in the water were; conductivity (26,567±464.28 µS/cm), total dissolved solids (TDS), (13,250±187.08 mg/L), total suspend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
2
8
1
Order By: Relevance
“…These parameters were however identified to insignificantly differ from the values recorded at the control site assessed in this study. Similar findings have also been reported in literature where reports of deranged physicochemical parameters have been reported to occur in relation to harmful oil and gas-related activities [23,25,26].…”
Section: Discussionsupporting
confidence: 91%
“…These parameters were however identified to insignificantly differ from the values recorded at the control site assessed in this study. Similar findings have also been reported in literature where reports of deranged physicochemical parameters have been reported to occur in relation to harmful oil and gas-related activities [23,25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Turbidity readings exceeded the BIS (5 NTU) limit at every site. High turbidity levels can harm the aquatic ecosystem by reducing light penetration, which lowers photosynthetic activity in aquatic plants and decreases the dissolved oxygen level in the water (Simeon et al, 2019). According to Central Pollution Control Board (CPCB) guidelines, the water quality of Malin River is classified as category E due to its turbidity levels, making it unsuitable for drinking, bathing, or irrigation.…”
Section: Turbiditymentioning
confidence: 99%
“…Ling et al (2016) found the pH level in Malaysia's Balui River to be between 6 and 7.7. Simeon et al (2019) recorded the pH of Silver River to be between 7.06 and 7.14. Our study found the pH range of the Malin River to be slightly acidic at site 2 and neutral at all other sites.…”
Section: Phmentioning
confidence: 99%
See 2 more Smart Citations